(3efGbH Cgd GdMbs - (3CHh eMeO Sgd Hf YHO Gddg GdJSJQj,J (B283 (3g` s ((3TgGH GdOjf GdSgQhQOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JfRg Yf GdTQjc hGdhRjQ hYf GdVO hGdfXjQ hHYO abO SCdJfi Cf CLeY dc eNJUQkG aiYde GdSdhc heYQaI MGd GdWGFaI s
(3BNQgG (B:s
(3hdbO cGf eYi QLd eZQHi hfMf HSGMd eUQ aPcQfG MOjK RjGOI GdfSd aYLH dPdc hMda Cf dGjSGaQ Edi HdOg MJi jWdY Gdfjd Je GdNhGU GdJi ai GdEfSGf hGdhdi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B143s
Keywords: (3GdJUha hGdBOGH GdTQYjIs